Acromegaly incidentally diagnosed at term in a pregnant woman presenting with ventricular premature complexes - Nair, Aiswarya K.; Sagili, Haritha; Dorairaj, Jayalakshmi; Parvathi, T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Pituitary adenomas lead to increased growth hormone production and acromegaly. Pregnancy in acromegaly is rare as spontaneous conception is affected. We presented a case of 31 year old lady conceived by ovulation induction and presented at term gestation with ventricular premature complexes and was subsequently diagnosed with pituitary micro adenoma causing acromegaly. There has been no reported case of pregnancy with acromegaly presenting with premature ventricular complexes. Moreover, diagnosis of acromegaly in pregnancy is difficult and limited literature is available on its effects as well as management.